BOOK REVIEWS (Heythrop journal, 1988)
Book reviewed in this article: Old Testament Criticism in the Nineteenth Century: England and Germany. By John Rogerson. The Prophetic Persona: Jeremiah and the Language of the Self (Journal for the Study of the Old Testament Supplement Series 32). By Timothy Polk. God's Prophet, Cod's Servant: A Study in Jeremiah and Isaiah 40–55. By John Goldingay. A History of Israel from the Beginnings to the Bar Kochba Revolt, AD 135. By J. Alberto Soggin. The New Testament as Canon: An Introduction. By Brevard S. Childs. Resurrection: New Testament Witness and Contemporary Reflection. By Pheme Perkins. II Corinthians (Anchor Bible 32A). Translation and Commentary by Victor Paul Furnish. Der leidende Gerechtfertigte (Wissenschaftliche Untersuchungen zum Neuen Testament, 2. Reihe, 13). By Karl Theodor Kleinknecht. Paul, Apostle to the Gentiles: Studies in Chronology. By Gerd Lüdemann, translated by F. Stanley Jones. The Older Testament: The Survival of Themes from the Ancient Royal Cult in Sectarian Judaism and Early Christianity. By Margaret Barker. Jews and Christians: Graeco-Roman Views (Cambridge Commentaries on Writings of the Jewish and Christian World 200 BC to AD 200: 6). By Molly Whittaker. The Jewish and Christian World 200 BC to AD 200 (Cambridge Commentaries on Writings of the Jewish and Christian World 200 BC to AD 200: 7). By A.R.C. Leaney. Die stadtrömischen Christen in den ersten beiden Jahrhunderten (Wissenschaftliche Untersuchungen zum Neuen Testament [2 Reihe] 18). By Peter Lampe. Christian Origins. By Christopher Rowland. The Rise of Christianity. By W.H.C. Frend. Saints and Sinners in the Early Church. By W.H.C. Frend. Pagan Rome and the Early Christians. By Stephen Benko. What Crucified Jesus? By Ellis Rivkin. The Byzantine Apocalyptic Tradition. By Paul J. Alexander, edited by Dorothy de F. Abrahamse. Die Synoden Englands bis 1066. By Hannah Vollrath. Jewish Bankers and the Holy See. From the Thirteenth to the Seventeenth Century (The Littman Library of Jewish Civilization). By Léon Poliakov, translated by Miriam Kochan. Judaism on Trial. Jewish-Christian Disputations in the Middle Ages (The Littman Library of Jewish Civilization). Edited and translated by Hyam Maccoby. The Jews of Islam. By Bernard Lewis. Human Rights in Jewish Law. By Haim Cohn. Crusade and Mission: European Approaches toward the Muslims. By Benjamin Z. Kedar. Lefèvre. Pioneer of Ecclesiastical Renewal in France. By Philip Edgcumbe Hughes. The Protestant Reformation in Ireland, 1590–1641 (Studies in the Intercultural History of Christianity 34). By Alan Ford. Galileo and his Sources: The Heritage of the Collegio Romano in Galileo's Science. By William A. Wallace. Politics and Language in Dryden's Poetry. By Steven N. Zwicker. The Anglican Tradition. Edited by Richard Holloway. The Anglican Church Today and Tomorrow. By Michael Marshall. Popular Catholicism in Nineteenth-century Germany. By Jonathan Sperber. The Russian Church under the Soviet Regime 1917–1982. By Dimitri Pospielovsky. Daniel Mannix and Ireland. By Colm Kiernan. The Vatican and Italian Fascism, 1929–32: A Study in Conflict. By John F. Pollard. The Vatican, the Bishops and Irish Politics 1919–39. By Dermot Keogh. Martin Buber: A Centenary Volume. Edited by Haim Gordon and Jochanan Bloch Religious Education: Philosophical Perspectives. By John Sealey. The Psychology of Moral Development. By Lawrence Kohlberg. Can Modern War Be Just? By James Turner Johnson. The Tragedy of Political Science: Politics, Scholarship and Democracy. By David M. Ricci. Metaphysics. By D.W. Hamlyn. Metaphysics: Its Structure and Function. By Stephan Körner. Plotinus, Enneads IV and V (Loeb Classical Library). Translated by A.H. Armstrong. Lectures‘chrétiennes’de Nietzsche. By Yves Ledure. Social Classes in Marxist Theory. By Allin Cottrell. Wittgenstein: A Critique. By J.N. Findlay. Erring: A Postmodern A/theology. By Mark C. Taylor. God of Chance. By David J. Bartholomew. Images of Christ: An Introduction to Christology. By Glenn F. Chesnut. Christology: Basic Texts in Focus. By Leopold Sabourin. The Divine Mother: A Trinitarian Theology of the Holy Spirit. By Donald L. Gelpi.